Histories of Dirt : Media and Urban Life in Colonial and Postcolonial Lagos - Newell, Stephanie, 1968- (Book collections on Project MUSE., 2020)
"HISTORIES OF DIRT IN WEST AFRICA is a historical and cultural approach to the study of dirt in relation to public health, governance, and daily life in urban West Africa. While in the Anglophone world dirt is evoked to denote a problem, Stephanie Newell broadens dirt as an interpretive category to move beyond the fixation on purity and cleanliness to encompass understandings of, and interactions with, dirt as a dimension of urbanization. Newell thus situates her study of dirt between the failings of colonial interpretations of dirt and the multifaceted connotations of dirt in the West African context. Through archival work, she asserts that dirt structured colonial understandings of public health, which then gradually enabled a discourse through which hygiene policies under the British Annexation of Lagos were set--the same logic that enabled racial segregation in the name of public health. Newell reads the deep history of "sanitary salvation," or the set of related public health initiatives meant to enable clean and healthy colonial subjects, against present-day discussions concerning health, well-being, and daily life in West African cities.